Yield Ratios of Isomeric Pairs \(^196m,g\)Au, \(^186m,g\)Ir, and \(^183m,g\)Os in the \(^197\)Au\((γ,xnyp)\) Reactions with 2.5 GeV Bremsstrahlung - Do, Nguyen Van; Tran, Dinh Trong; Kim, Tien Thanh; Pham, Duc Khue; Lee, Hee-Seok; Kim, Guinyun (Communications in Physics, 2022)
The yield ratios of high to low spin states of the 196m,gAu, 186m,gIr, and 183m,gOs isomeric pairs produced by 197Au(γ,xnyp) reactions with a bremsstrahlung end-point energy of 2.5 GeV have been measured. Measurements were performed by the activation method in combination with off-line γ-ray spectrometry. The induced activity of the studied radionuclides was derived from the photo-peak area of the selected γ-ray after making the necessary corrections. The isomeric yield ratios obtained in this work are the first measurement. The relationships between the yield ratios of studied isomeric pairs with the value of high spin states, the spin difference between the high spin states and the target nucleus, and the number of nucleons emitted from the target nucleus are discussed.